Lateral Reliability Assessment of Eccentrically Braced Frames Including Horizontal and Vertical Links Under Seismic Loading - Abdelhamid, F.; Yahiaoui, D.; Saadi, M.; Lahbari, N. (Engineering, Technology & Applied Science Research, 2022)
Eccentrically Braced Frames (EBFs) have been widely used in the last decades and proved their efficiency to resist strong earthquake intensities by providing suitable ductility and lateral stiffness. Using the PBPD method for the design, EBFs can fulfill the target performance objectives under major earthquakes. The most commonly used configurations are the K-shaped and the recent Y-shaped EBFs, which have the advantage that the links are independent of the beam and can be easily replaced after an earthquake without serious damage to the beam and slab. This study focused on the lateral reliability of both systems under seismic loading. Nonlinear static pushover and Incremental Dynamic Analysis (IDA) were performed on 5-story and 10-story K- and Y-shaped EBFs. A series of 14 near- and 7 far-field seismic records were considered to analyze and compare the inter-story drifts of both systems using the Seismostruct software. Moreover, Peak Ground Accelerations (PGA) and the different performance levels were also examined.